Employee recruitment : strategies for greater attraction - Muthiah, Vellayadevan (1998)
The research was concerned with the proper implementation of recruitment exercise in an organization. The purpose of the study was to understand the scope of recruitment exercise and the planning of greater strategies in order to conduct employees recruitment exercise effectively to attract employees into the organisation. The study also explored the challenges faced by the organizations in conducting recruitment exercises. Six respondents were interviewed in this study. They were the human resource managers, employees who left the organization to join other organizations and employees who have served for a period of less than two years in the same organizations. Each interview lasted for about an hour. All interviews were tape-recorded and subsequently transcribed to facilitate data analysis. It was found that most respondents believed that recruitment is a continuos process. They also believed that the human resource managers should understand the scope of recruitment process such as manpower planning, selection, interviews, orientation, training and appraisal. One of the reasons why companies fail to recruit and attract employees is the narrow scope of recruitment process. Organizations also fail to relate the management practices with recruitment exercise. Beside implementing the recruitment process effectively, the management practices also equally important in attracting employees into the organization. Compensation & benefit, communication, job satisfaction, working environment, training and career development are equally important to attract employees into the organization. Employees prefer to check on the organization's practices before they join the organization. These practices could attract employees join the organization. Consistent to the literature, the respondents also stressed that the recruitment process must be effectively conducted and the management practices must be related to the recruitment exercise. A effective way of attracting employees is necessary in order employ the right candidates. The organisation should able to relate management practices and policies while planning to conduct recruitment exercise. The recruitment process must be effectively implemented in order to attract employees into the organisation. A framework for improving the practice of recruitment and attracting employees was made with specific recommendation for policy and future research.